Can Union Voice Make a Difference? The Effect of Union Citizenship Behavior on Employee Absence. Issue 2 (29th October 2013) - Deery, Stephen J.; Iverson, Roderick D.; Buttigieg, Donna M.; Zatzick, Christopher D.; Townsend, Keith; Wilkinson, Adrian
Abstract The interests of organizations and unions are often seen to be in competition. However, the union‐voice hypothesis suggests that unions can provide a distinctive mechanism to lower organizational costs by reducing exit behavior. This study looks at union citizenship behavior as a form of voice and examines its effect on employee absence. It draws on data from 367 branches of a large unionized banking organization to explore both the antecedents and outcomes of union citizenship behavior. Union citizenship behavior directed toward helping fellow members with workplace grievances was found to reduce branch‐level absenteeism, while union loyalty mediated the impact of a number of union‐related variables on union citizenship behavior. The implications for a balanced union‐management relationship are discussed in the article. © 2013 Wiley Periodicals, Inc.